Converge - Lord, Bob; Velez, Ray (Ascent Audio, 2020)
Using Razorfish client examples (such as AXE, Intel, Mercedes-Benz, Samsung, Delta, and Kellogg) Ray and Bob will share their first-hand experience of working intimately with clients to solve business problems at the collision point between customers, technology and marketing. Throughout the narrative, Bob and Ray will provide the reader a roadmap to replicate their success within their own organization; how to market in a world of constant change, how to organize for innovation, how to innovate faster use the principals of agile development across your business, etc. The first half of the book will cover the following topics: The collision: why and how technology, media, and creativity are converging and how this has revolutionized marketing and business strategy The consumer voice: why and how media has changed what to expect in the future (client examples) Next generation storytelling: why and how creativity has changed, and what to expect in the future (client examples) The second half of the book will be focused on explaining answers to the problems our customers are dying to have solved: Part 1 - How to create religion around merging technology and marketing within your organization (how to tell the story, who to tell it to, why should they believe, etc.) Part 2 - How to change your organizational structure to leverage marketing/tech convergence (breaking down silos, cross-training, etc.) Part 3 - How to empower your people to leverage convergence (create business entrepreneurial ownership, adjust compensation/incentive structure/goals/objectives, alignment against client need, etc.) Part 4 - How to change your processes to leverage convergence (how to apply agile methodology principals across all marketing functions, etc.).